ÐšÑ€Ð¸Ð¾Ñ‚ÐµÑ€Ð¼Ð¾ÑÐ°Ð½Ð°Ñ†Ð¸Ñ Ð¸ Ð¾Ð·Ð¾Ð½Ð¾Ñ‚ÐµÑ€Ð°Ð¿Ð¸Ñ Ð¾Ñ‡Ð°Ð³Ð¾Ð² Ð´ÐµÑÑ‚Ñ€ÑƒÐºÑ‚Ð¸Ð²Ð½Ð¾Ð³Ð¾ Ñ‚ÑƒÐ±ÐµÑ€ÐºÑƒÐ»ÐµÐ·Ð° Ð¿Ð¾Ñ‡ÐµÐº - Kozin, Yu. I. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
The possibility and efficiency of intraorgan disinfection, sanation and regeneration of the tuberculosis destruction foci at a combined use of supralow and increased temperatures with ozone therapy has been studied. There are presented the results of tolerance for different freezing and thawing temperature regimens for 446 â€œAcademiaâ€ strains and 343 â€œhospitalâ€ medicinal-resistance strains of mycobacteria of tuberculosis, as well asthe efficiency of intraorgan sanation of cavernous forms of nephrotuberculosis by means of cryothermocycling in 120 breedless dogs. With various laboratory, histological, X-ray structural and functional methods there was proved that the ones of intracavernous cryoeffect under established optimal parameters enable using the atraumatic miniinvasive methods to reach the guaranteed abacillation of caseous-necrotic masses with stimulation of resorption- regenerative ability of structural components of kidney tissue. Ozone oxygen mixture and the solutions significantly increase the efficiency of treatment of destructive-cavernous forms of tuberculosis.